Adult hippocampal neurogenesis and antidepressants effects. (February 2020) - Planchez, Barbara; Surget, Alexandre; Belzung, Catherine
Abstract : The hippocampus is particularly involved in cognitive processes and is a key regulator of stress responses and emotions. Therefore, the role of adult-born neurons in this region has become a crucial field of research in order to understand mood and stress disorders, such as major depression. Many studies have characterized the role of these neurons in cognition, mood regulation and antidepressant actions. Nevertheless, the precise mechanisms underpinning these antidepressant effects remain unclear. In this review, we first discuss the effects of stress and antidepressant treatments on adult-born neurons, and subsequently, the role and mechanisms of neurogenesis in antidepressant action. Some studies have shown that adult-born neurons could affect overall hippocampal activity, thus normalizing the latter which could restore neuronal pathways underlying antidepressant effects.